Perbedaan Kapasitas Vital Paksa Paru Tenaga Kerja pada Lokasi Pengecoran/ Pencetakan dan Lokasi Pengikiran/Pembubutan di Industri Kerajinan Cor Aluminium â€œEDâ€ Giwangan Yogyakarta. - Ekawati, Ekawati; Suwondo, Ari (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2005)
ABSTRACT Background: Dust pollution can be exist at production process on industry, include on â€œEDâ€ aluminium cast indust, Yogyakarta which is on the production process included foundry and fitting-shop process. Aluminium dust can influence lung function of the worker. The aim of this research was to study the difference of forced vital capacity (FVC) on workers between foundry and fitting-shop in â€œEDâ€ aluminium cast industry, Giwangan Yogyakarta. Method: This was an observational research using cross sectional design. The population was 15 workers on each location. The data was collected using questionnaire, measuring of lung function and total dust content. The data would be analyzed using Mann-Whitney test. Result: The result showed that the average of total dust content on those location was 0.65 mg/m3 and 2.75 mg/m3 orderly. This was still below the threshold value (10 mg/m3). The measuring of lung function showed that 73.35% of workers in foundry Â and 66.6% of workers in fitting-shop hadÂ FVC decreasing with the average of FVC was 75.80% and 77.27% in order. The statistic test showed that there was no significant difference of FVC between Â those workers. Conclusion: No significant difference of FVC on workers between foundry and fitting-shop in â€œEDâ€ aluminium cast industry, Giwangan Yogyakarta. Â Key Words: Forced Vital Capacity, workers, foundry, fitting-shop.